Seventeenth-century Malay wordlists and their potential for etymological scholarship - Hoogervorst, Tom G. (UI Scholars Hub, 2024)
Early-modern wordlists and dictionaries provide an underexplored area for etymological scholarship. By critically comparing different sources written under the aegis of the Dutch East India Company, often compiled by autodidacts who were unable to gain fluency, this article makes some generalizations about the etymology and contact history of early-seventeenth-century Malay. I demonstrate that the Dutch materials provide concrete instances to study lexical change, both phonologically and semantically. When used advisedly, the material also casts light on the nature of language contact in an era in which the Indo-Malayan Archipelago was at the nexus of trade networks connecting speakers of Arabic, Persian, Chinese, Portuguese, and various Indian and Indonesian languages. Finally, early-modern lexicography offers valuable data to reconstruct elements of the society being studied, including in the realms of religion, social hierarchies, and material culture.